2020
DOI: 10.1109/access.2020.3030751
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Spam Email With Machine Learning Optimized With Bio-Inspired Metaheuristic Algorithms

Abstract: Electronic mail has eased communication methods for many organisations as well as individuals. This method is exploited for fraudulent gain by spammers through sending unsolicited emails. This paper aims to present a method for detection of spam emails with machine learning algorithms that are optimized with bio-inspired methods. A literature review is carried to explore the efficient methods applied on different datasets to achieve good results. An extensive research was done to implement machine learning mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 17 publications
0
37
0
5
Order By: Relevance
“…The article [228] explores bio-inspired methods to analyze email datasets. Multiple ML models including Naive Bayes, SVM, Random Forest,Decision Trees, and Multilayer Perceptron were considered in [228] to evaluate these datasets.…”
Section: Bio-inspired Aimentioning
confidence: 99%
“…The article [228] explores bio-inspired methods to analyze email datasets. Multiple ML models including Naive Bayes, SVM, Random Forest,Decision Trees, and Multilayer Perceptron were considered in [228] to evaluate these datasets.…”
Section: Bio-inspired Aimentioning
confidence: 99%
“…x t+1 ir 1 = x t r 1 (11) The E3GOA algorithm is the third algorithm proposed in this work and is shown in Algorithm 4. This algorithm is similar to the previous proposed algorithms but with a slight modification in the mutation operator.…”
Section: B the Enhanced Goa Algorithmmentioning
confidence: 99%
“…All the above techniques are based mainly on two basic approaches: a Machine Learning approach and a knowledge engineering approach [11]. The knowledge engineering approach is called rule-based filtering, which creates a set of rules by using rule-based spam filtering tools or by some other authority [12].…”
Section: Introductionmentioning
confidence: 99%
“…The performed research showed that the NB gave the best results, but expressed a limitation due to classconditional independence. Gibson et al [19] analyzed machine-learning algorithms that are optimized with bio-inspired methods. They implemented Multinominal Naïve Bayes (MNB), SVM, RF, DT, and Multilayer Perceptron algorithms which were tested on seven different e-mail datasets: Lingspam, PUA, PU1, PU2, PU3, Enron, and SpamAssassin.…”
Section: Related Workmentioning
confidence: 99%